1994
DOI: 10.1093/ajcp/102.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Coccoid Forms ofHelicobacter pyloriin the Human Stomach

Abstract: Helicobacter pylori (HP) may transform from helical bacillary forms to coccoid forms after several days' in vitro incubation. The authors examined 111 consecutive gastrectomy specimens for the presence of coccoid forms of H pylori. Tissues from 64 stomachs (57.7%) showed colonization by H pylori, including 49 cases (76.6%) of adenocarcinoma, 14 cases (21.9%) of benign peptic ulcer, and 1 case (1.6%) of malignant lymphoma. Of these, coccoid forms of H pylori were identified in 53 cases (82.8%). In hematoxylin-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
93
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 14 publications
0
93
0
1
Order By: Relevance
“…Coccoid H. pylori maintains the same antigenic characteristics as the bacillary form. 41 In addition, experimental animal models indicate that the coccoid form of H. pylori reverts to the bacillary form and induces gastritis and ulcer. 42 Successful culture of H. pylori from the gastric lymph nodes suggests that some of H. pylori-positive macrophages at the paracortical areas may have carried coccoid forms of H. pylori.…”
Section: Intestinal Metaplasiamentioning
confidence: 99%
“…Coccoid H. pylori maintains the same antigenic characteristics as the bacillary form. 41 In addition, experimental animal models indicate that the coccoid form of H. pylori reverts to the bacillary form and induces gastritis and ulcer. 42 Successful culture of H. pylori from the gastric lymph nodes suggests that some of H. pylori-positive macrophages at the paracortical areas may have carried coccoid forms of H. pylori.…”
Section: Intestinal Metaplasiamentioning
confidence: 99%
“…Growing evidence supports the concept that H. pylori exists in two viable forms, spiral or coccoid, and several studies have shown that the coccoid form cannot be cultured or be detected by RUT or histology but can be detected PCR (Bode et al, 1993;Chan et al, 1994;Hulten et al, 1996;Moayyedi and Dixon, 1998;He et al, 2002). Consequently, another possible explanation for our findings could be a high percentage of the coccoid form of H. pylori as a result of antibiotic treatment in the patients from group B. Additionally, He et al (2002) have suggested the possibility that no viable H. pylori were present in the biopsy sample but only dead bacteria or chromosomal DNA.…”
mentioning
confidence: 93%
“…The role of the coccoid form in pathogenesis of H. pylori-associated gastritis has been disputed. Some authors consider the coccoid form as a degenerative or dead form of H. pylori [ 16,21,25], while others consider it as a resting but still metabolic active form [2, 3,12,22,29,321. The aim of this study was to demonstrate the conversion of spiral form of H. pylon to coccoid forms, and to show both degenerative and intact subcellar morphology suggesting that some of the coccoid bacteria may be viable.…”
Section: Introductionmentioning
confidence: 99%